Tropisetron in the prevention of chemotherapy-induced acute emesis in pediatric patients - Mutafoğlu Uysal, Kamer; Olgun, Nur; Sarıalioglu, Faik (The Turkish Journal of Pediatrics, 1999)
We evaluated the antiemetic efficacy of tropisetron for control of acute emesis during grade 3 or 4 emetogenic chemotherapy in children. Tropisetron was administered as a single intravenous dose of 0.2 mg/kg on the first day and intravenously or orally with the same dose on subsequent days. A total of 125 courses of highly emetogenic chemotherapy was administered to 22 children with a median age of 14 years (range: 3-18 years). All 22 patients received tropisetron for at least two courses. Overall complete response on day I was observed in 80 out of 125 courses (64%). The response rates were consistent over multiple courses; a complete and major response rate on the first day of Course I (n: 22 courses) and Course II (n: 22 courses) was observed in 73 and 77 percent of cases, respectively. When the results were analyzed according to the daily schedules, overall complete response for grade 4, grade 3 and grade 1-2 emetogenic treatment days was 59, 85 and 75 percent, respectively. In this study, cost effectiveness for tropisetron was also determined; the cost per successfully controlled course was 162 USD. No side effects of tropisetron other than mild diarrhea and dry-mouth were documented in this study. In conclusion, the results of this study confirmed that tropisetron is a safe, well tolerated and effective antiemetic drug for the prevention of acute emesis in children and adolescents during highly emetogenic chemotherapy.